High Serum Carbohydrate Antigen (CA) 125 Level Is Associated With Poor Prognosis in Patients With Light-Chain Cardiac Amyloidosis - Li, Muzheng; Wu, Zhijian; Tudahun, Ilyas; Liu, Na; Lin, Qiuzhen; Liu, Jiang; Wang, Yingmin; Chen, Mingxian; Chen, Yaqin; Qi, Nenghua; Zhu, Qingyi; Li, JunLi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Patients with light-chain cardiac amyloidosis (AL-CA) are characterized by high levels of serum carbohydrate antigen 125 (CA 125). However, studies have not explored the correlation between CA 125 and AL-CA. The aim of this study was to explore the clinical implications of an increase in CA 125 in patients with AL-CA. Methods and Results: A total of 95 patients diagnosed with AL-CA at the Second Xiangya Hospital were enrolled in this study. Out of the 95 patients with AL-CA, 57 (60%) patients had elevated serum CA 125 levels. The mean age was 59.7 ± 10.0 years with 44 (77.2%) men in the high serum CA 125 group, and 61.8 ± 9.6 years with 28 (73.7%) men in the normal group. Patients with high CA 125 showed higher rates of polyserositis (79.3% vs. 60.5%, p = 0.03), higher levels of hemoglobin (117.4 ± 21.9 g/L vs. 106.08 ± 25.1 g/L, p = 0.03), serum potassium (4.11 ± 0.47 mmol/L vs. 3.97 ± 0.40 mmol/L, p = 0.049), low-density lipoprotein-cholesterol (3.0 ± 1.6 mmol/L vs. 2.3 ± 1.10 mmol/L, p = 0.01), and cardiac troponin T (96.0 pg/mL vs. 91.9 pg/mL, p = 0.005). The median overall survival times for patients with high or normal serum CA 125 were 5 and 25 months, respectively (p = 0.045). Multivariate Cox hazard analysis showed that treatment without chemotherapy (HR 1.694, 95% CI 1.121–2.562, p = 0.012) and CA 125 (HR 1.002, 95% CI 1.000–1.004, p = 0.020) was correlated with high all-cause mortality. The time-dependent receiver operating characteristic (t-ROC) curve showed that the prediction accuracy of CA 125 was not inferior to that of cardiac troponin T, N-terminal pro-B-type natriuretic peptide (NT-proBNP), and lactate dehydrogenase (LDH) based on the area under the curve. Conclusions: CA 125 is a novel prognostic predictor. High serum CA 125 values are correlated with low overall survival, and the accuracy of predicting prognosis is similar to that of traditional biomarkers in AL-CA.